2019
DOI: 10.1111/acer.14214
|View full text |Cite
|
Sign up to set email alerts
|

Wake Forest Alcohol Imagery Set: Development and Validation of a Large Standardized Alcohol Imagery Dataset

Abstract: Background: The study of alcohol use frequency utilizes alcohol-related cue imagery. Although a number of alcohol-image databases currently exist, they have several limitations: Many are not publicly available, some use stock images or clip art rather than real photographs, several eliminate any photographs displaying brand information, and predominantly they contain relatively few images. The aim of this project was to develop a large, open-access database of alcohol-related cue images, containing photographs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, researchers should report stimulus validation procedures routinely. Where possible, researchers can make use of existing validated stimulus sets [44,[66][67][68][69], and in situations where this is inappropriate (e.g. cultural differences in drinking preferences, brand familiarity) available guidelines (see [44]) should be utilized to develop new sets.…”
Section: Raising the Bar: Recommendations For Researchersmentioning
confidence: 99%
“…Furthermore, researchers should report stimulus validation procedures routinely. Where possible, researchers can make use of existing validated stimulus sets [44,[66][67][68][69], and in situations where this is inappropriate (e.g. cultural differences in drinking preferences, brand familiarity) available guidelines (see [44]) should be utilized to develop new sets.…”
Section: Raising the Bar: Recommendations For Researchersmentioning
confidence: 99%
“…We propose the development of a web-based application, incorporating in-built quality assurance methods and validated inventories. Our review revealed that a large proportion of studies assessed psychiatric symptoms in total or relative isolation (Cunningham et al, 2017a;Cunningham et al, 2017b;Halkjelsvik, 2021;Moody et al, 2017;Peterson et al, 2019;Strickland and Stoops, 2018;Tilden et al, 2020). It is long-established that psychiatric symptoms and diagnoses interact and overlap (Gillan and Daw, 2016;Zimmerman and Mattia, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…We propose the development of a web-based application, incorporating in-built quality assurance methods and validated inventories. Our review revealed that a large proportion of studies assessed psychiatric symptoms in total or relative isolation (Cunningham et al, 2017a;Cunningham et al, 2017b;Halkjelsvik, 2021;Moody et al, 2017;Peterson et al, 2019;Strickland and Stoops, 2018;Tilden et al, 2020). It is long-established that psychiatric symptoms and diagnoses interact and overlap (Gillan and Daw, 2016;Zimmerman and Mattia, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…For example, Clarke et al (2021) used one criterion of attention-check items and excluded 0.2% of their sample. Peterson et al (2019) used two criteria of attention-check and bot detection, resulting in an exclusion of 28.3% of their sample. Ophir et al (2020) applied three attention-check criteria of infrequency items, reading speed, and participant internal consistency, and filtered suspicious IP addresses, excluding 31.4% of their sample.…”
Section: Discussionmentioning
confidence: 99%